Measuring the Orbital Angular Momentum of Light Based on Optical Differentiation - Liang Fang; Lan Luo; Rujin Zhao; Bo Liu (IEEE Photonics Journal, 2023)
The utilization of orbital angular momentum (OAM) in light for information encoding is a promising avenue, as it exhibits resilience against environmental disturbances. However, the direct detection of OAM poses a significant challenge due to beam distortion during transmission, which ultimately limits the practical application of OAM-based optical communication. We propose an environmentally friendly and intuitive detection method based on optical differentiation using a weak-measurement system. Optical differential measurements were conducted on Laguerre-Gaussian beams (L-G beams) with $l$ = 5 and $l$ = 8 to validate the feasibility of this approach. This approach mitigates the impact of disturbances on OAM measurement, enabling direct detection through a simplified system, which serves as a valuable reference for utilizing OAM as an information carrier in free-space optical communication.